Challenges in IPF diagnosis, current management and future perspectives: Patient case 1 - Egan, Jim (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Patient presentation and diagnosisA 78-year-old female was referred to our department in April 2011 with shortness of breath. Clinical examination revealed bilateral limited crackles but no signs of finger clubbing. Lung function evaluation showed a percent predicted FVC of 78 and DLco of 67. The patient underwent HRCT imaging which showed cardinal features of a UIP pattern enabling a rapid diagnosis of IPF without the need for surgical lung biopsy.[...]